Diuron Multilayer Adsorption on Activated Carbon from CO2 Activation of Grape Seeds. Issue 1 (2nd January 2016) - Bahri, M. Al; Calvo, L.; Gilarranz, M. A.; Rodriguez, J. J.
Abstract : Granular activated carbons were obtained from grape seeds by pyrolysis at 600°C and subsequent physical activation with CO2 (750–900°C, 1–3 h, 25–74% burn-off). The carbon and ash content increased during the activation, reaching values of 79.0% and 11.4%, respectively. Essentially microporous materials with BET surface areas between 380 and 714 m 2 /g were obtained. The performance of the activated carbon in the adsorption of diuron in aqueous phase was studied within the 15–45°C temperature range. Equilibrium data showed that the maximum uptake increased with temperature from 120 to 470 µmol/g, also evidencing some dependence of the adsorption mechanism on temperature. Data were fitted to five isotherm models [Langmuir, Freundlich, Dubinin–Radushkevich, BET, and GAB (Guggenheim, Anderson, and de Boer)]. Kinetic data were analyzed using first- and second-order rate equations and intraparticle diffusion model. The second-order rate constant values obtained (2.8–13.5 × 10 −3 g/µmol min) showed that the hollow core morphology of the material favors the adsorption kinetics.